2014
DOI: 10.1002/ajh.23889
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral therapy is associated with a better survival in patients with hepatitis C virus and B‐cell non‐Hodgkin lymphomas, ANRS HC‐13 lympho‐C study

Abstract: on behalf of the ANRS HC-13 Lympho-C Study Group Hepatitis C virus (HCV) infection increases the risk of B-cell non-Hodgkin lymphomas (B-NHL). Antiviral treatment (AT) can induce hematological responses in patients with marginal zone lymphomas (MZL). The ANRS HC-13 Lympho-C study aimed at a better understanding of the impact of AT on HCV associated B-NHL. This multicentric study enrolled 116 HCV-positive patients with B-NHL between 2006 and 2012. Cytological and histological samples were collected for centrali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
100
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 30 publications
7
100
0
2
Order By: Relevance
“…Severe hepatotoxicity occurred in 14% of patients but was not associated with the use of RTX. 54 A recent prospective study including 45 patients with HCV infection and DLBCL, all treated with R-CHOP, found a 3-year OS of 73%, 55 which is similar to the results found in HCV-negative DLBCL treated with R-CHOP. Antiviral therapy following CT-induced NHL remission permits to achieve a prolonged disease-free survival (P = .038).…”
Section: Hcv-induced Dlbclsupporting
confidence: 67%
“…Severe hepatotoxicity occurred in 14% of patients but was not associated with the use of RTX. 54 A recent prospective study including 45 patients with HCV infection and DLBCL, all treated with R-CHOP, found a 3-year OS of 73%, 55 which is similar to the results found in HCV-negative DLBCL treated with R-CHOP. Antiviral therapy following CT-induced NHL remission permits to achieve a prolonged disease-free survival (P = .038).…”
Section: Hcv-induced Dlbclsupporting
confidence: 67%
“…Interestingly, the presence of these mutations was associated with a shorter overall survival (OS) and with the presence in the diagnostic biopsy of a small cell component that suggests a possible histologic transformation of the DLBCL [Arcaini et al 2015]. It is already known that NOTCH is a pathway involved in the pathogenesis of SMZL: this finding seems to correlate with the observation that a high proportion of DLBCLs in HCV-positive individuals can arise from a preceding MZL [Besson et al 2006;Michot et al 2015].…”
Section: What Evidence Comes From Epidemiological Studies Linking Nhlsupporting
confidence: 56%
“…Some distinctive characteristics can however be highlighted, which may be, at least in part, attributable to the presence of the HCV infection itself. First, patients who are HCV-positive more frequently present high transaminase levels, monoclonal gammopathies, autoimmune phenomena, rheumatoid factor and asymptomatic cryoglobulinemia [Musto, 2002;Michot et al 2015]. Second, at presentation, the involvement of the spleen or extranodal sites, which are also common target organs of HCV (i.e.…”
Section: Are There Peculiar Clinical Features Of Hcv-associated Lymphmentioning
confidence: 99%
“…3 Whether these effects are due to HCV clearance or to an antiproliferative effect of interferon remains unknown. We describe a patient with a complete hematologic response of an HCV-associated disseminated marginal zone lymphoma (MZL) to an interferon-free anti-HCV treatment.…”
mentioning
confidence: 99%
“…4 Moreover, interferon-based antiviral treatment has been shown to improve the prognosis of HCV patients with B-cell lymphomas. 3 The underlying mechanism is still debated, with a potential antiviral and/or antiproliferative effect of interferon.…”
mentioning
confidence: 99%